Maternal hemodynamic effect of prophylactic glycopyrrolate after spinal anaesthesia for elective caesarean section - Piya, Roshan; Shrestha, Anil; Pradhan, Manisha; Amatya, Shirish; Hirachan, Niroj; Ghimire, Binam (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Hypotension and bradycardia are the most common complications during spinal anesthesia. Bradycardia decreases cardiac output, resulting in hypotension and even cardiac arrest. Glycopyrronium, an anticholinergic drug increases heart rate and prevents bradycardia during spinal anesthesia by blocking the effects of acetylcholine on the sinoatrial node. The study aims to measure the maternal hemodynamic effect of glycopyrrolate after spinal anesthesia for elective caesarean section. Method: An intervention, comparative study was conducted in Patan Hospital after approval from Ethical Committee. Eighty-two pregnant women scheduled for elective caesarean section were randomly assigned in two groups by sealed envelope method; Group I received glycopyrrolate 0.2mg intravenous, Group II did not receive glycopyrrolate. The patient’s heart rate, blood pressure, mean arterial pressure, a total dose of ephedrine, the occurrence of nausea, vomiting, and dry mouth were recorded. Independent-T test, chi-square test were used for statistical analysis. Result: Among 82 elective caesarean sections, 41 in each group, Group II (non-glycopyrrolate) reported increased heart rate compared to Group I (glycopyrrolate), but was statistically not significant. The highest recorded diastolic blood pressure was more in Group I compared to Group II and was statistically significant. The highest recorded Mean Arterial Pressure was high in the glycopyrrolate group and was statistically significant. The total dose of ephedrine was lower in the statistically significant glycopyrrolate group. The incidence of dry mouth was more in the glycopyrrolate group and the difference was statistically significant. Conclusion: Glycopyrrolate reduces the incidence of hypotension but not bradycardia and decreases the need for vasopressor.